Foraging with finesse: A hard‐fruit‐eating primate selects the weakest areas as bite sites. Issue 1 (27th January 2016) - Barnett, Adrian A.; Bezerra, Bruna M.; Santos, Paulo J. P.; Spironello, Wilson R.; Shaw, Peter J.A.; MacLarnon, Ann; Ross, Caroline
ABSTRACT: Objectives: Fruit husks are rarely uniformly hard, varying in penetrability via sulci and changes in thickness. We tested whether a hard‐food specialist primate i) bites randomly on food fruit husk surfaces to access seeds, or ii) selects areas most easily penetrated by canines. We consider this would occur so as to minimize deployed mechanical force, energetic expenditure and risk of dental breakage when feeding. Methods: A sulcus is the natural line of weakness where a dehiscent fruit breaks open. Using fruits dentally opened for seeds by golden‐back uacaris ( Cacajao ouakary ) we: 1) analysed bite mark distribution on surface of four fruits types (hard‐with‐sulcus, soft‐with‐sulcus, hard‐no‐sulcus, soft‐no‐sulcus); 2) quantified the force needed to penetrate hard and soft fruits at sulci and elsewhere on fruit surface; 3) measured fruit wall thickness and correlated it with bite‐mark distribution in all four categories of fruit. Results: 1) Bite marks were distributed at random only on surfaces of soft fruits. For other fruits types, bite locations were concentrated at the thinnest areas of husk, either over the entire surface (non‐sulcate fruits), or at sulci (sulcate fruits). 2) For hard‐husked fruits, areas where uacaris concentrated their bites were significantly easier to penetrate than those where they did not. Conclusions: This hard‐fruit feeding specialist primate is not biting at random on the surface of diet fruits. To access seeds they are focusing on those areas requiring less force to penetrate. This may be to save energy, to minimize the risk of breaking teeth used in food processing, or a combination of both. The study shows, for the first time, the subtlety by which these powerfully‐jawed animals process their diet items. Am J Phys Anthropol 160:113–125, 2016. © 2016 Wiley Periodicals, Inc.